2013
DOI: 10.1051/0004-6361/201321169
|View full text |Cite
|
Sign up to set email alerts
|

Direct-imaging discovery of a 12–14 Jupiter-mass object orbiting a young binary system of very low-mass stars

Abstract: Context. Though only a handful of extrasolar planets have been discovered via direct-imaging, each of these discoveries had a tremendous impact on our understanding of planetary formation, stellar formation, and cool atmosphere physics. Aims. Since many of these newly imaged giant planets orbit massive A or even B stars, we investigate whether giant planets could be found orbiting low-mass stars at large separations. Methods. We have been conducting an adaptive optic imaging survey to search for planetary-mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 43 publications
7
118
0
Order By: Relevance
“…Delorme et al (2013) reported the discovery of a 12−14 M Jup orbiting a pair of young (30 Myr) late M-dwarfs (2M01033563-5515561) at a projected separation of 84 AU (system at 42 pc). Later on, Rameau et al (2013b) detected a probable 4 − 5 M Jup companion to the young (10 − 17 Myr) A star HD 95086 at a projected separation of 56 AU.…”
Section: Occurrence Of Giant Planets As a Function Of The Stellar Massmentioning
confidence: 99%
“…Delorme et al (2013) reported the discovery of a 12−14 M Jup orbiting a pair of young (30 Myr) late M-dwarfs (2M01033563-5515561) at a projected separation of 84 AU (system at 42 pc). Later on, Rameau et al (2013b) detected a probable 4 − 5 M Jup companion to the young (10 − 17 Myr) A star HD 95086 at a projected separation of 56 AU.…”
Section: Occurrence Of Giant Planets As a Function Of The Stellar Massmentioning
confidence: 99%
“…Advances in high-contrast and high-resolution imaging in the NIR (1-5 µm) led to the discovery of late-type companions to young nearby stars straddling the planet/BD boundary (e.g., Chauvin et al 2004Chauvin et al , 2005Lafrenière et al 2008;Marois et al 2008Marois et al , 2010Lagrange et al 2010;Ireland et al 2011;Delorme et al 2013;Rameau et al 2013;Kuzuhara et al 2013;Currie et al 2014). Most of these objects have estimated effective temperatures similar to those of L dwarfs.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded from the list the massive planets or brown dwarfs in a wide orbit (a p > 80 a.u.) that were discovered by direct imaging (Ros 458 b, SR 12 c, 2MASS0103, FW Tau b and ROXs 42B b; Burgasser et al 2010;Kuzuhara et al 2011;Delorme et al 2013;Kraus et al 2014), because the large separation from the central stars makes the effects discussed here absolutely negligible. We also excluded binary systems with cataclysmic variables or white dwarfs (PSR B1620-26, HU Aqr, HW Vir, NN Ser, DP Leo, UZ For, RR Cae, and NY Vir; Sigurdsson et al 2003;Hinse et al 2012;Beuermann et al 2010Beuermann et al , 2011Beuermann et al , 2012Potter et al 2011;Qian et al 2012a,b), because the common-envelope evolution of the central system would cause a different astrophysical situation.…”
Section: Application To Current Circumbinary Planetsmentioning
confidence: 84%